Penyuluhan Inovasi Produk Puding jagung dan Kacang Hijau Untuk Pencegahan Stunting - Fitriyah, Sabilatul; Syarifuddin, Muhammad Afif; Sari, Dian Puspita; Setia, Devit; Sulistiawati, Sulistiawati; Masruroh, Masruroh (Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting is a chronic nutritional problem still challenging in various rural areas of Indonesia, including Trosono Village in Lamongan. Efforts to prevent stunting require appropriate nutritional interventions, including introducing innovative and nutritious local food products. The purpose of this community service is expected to increase the knowledge of the Trosono Village community regarding the importance of balanced nutrition through innovative products such as corn and green bean pudding. The method of community service is divided into four stages, namely: First: Nutrition survey, Second: Recipe development, third: counseling and stage four, distribution and monitoring. The results after the implementation of the counseling program showed an increase in nutritional status in 17 children who experienced a significant increase in weight and height growth as indicators.